Content of food advertising for young adolescents on television - Setu Gupta; Swati Kalra; Jaya Shankar Kaushik; Piyush Gupta (Wolters Kluwer Medknow Publications, 2017)
Background: Food related advertisements on television may have a major influence on the dietary habits and obesity among young adolescents. Objective: To evaluate the frequency and typology of food advertisements on most popular television channels, watched by school-going young adolescents in Delhi. Methodology: Biphasic study to (a) identify the three television channels most frequently watched by administering a questionnaire to 400 school going young adolescents; and (b) view each of these channels for 2 hours per day for 6 days each, and observe the content of advertisements related to foods, beverages, and food outlets. Results: Four hundred and three food related advertisements were viewed over 36 hour on Discovery, MTV and Disney Channels. Among 235 food related advertisements 163 (69.3%) pertained to candies, chocolates and confectionary and 35 (14.8%) to salty snacks. Sugar sweetened soft drinks contributed 90 of 106 (85%) of beverage advertisements. Of 62 advertisements related to food outlets, 59 were of fast food joints. Conclusion: Majority of food advertising content on television most commonly watched by young adolescents is related to unhealthy foods and beverages, igh in energy and low in micronutrient content.